Expected and unexpected consequences of childbearing - a methodologically and politically important distinction that is overlooked - Øystein Kravdal (University of Oslo, Department of Economics, 2016)
Some consequences of childbearing are partly expected by the parents, while others clearly are difficult or impossible to foresee. In this paper, the different types of consequences, for parents or siblings, are briefly reviewed. It is then argued that if an effect of childbearing to a large extent is expected, varies between families, and is taken into account in the fertility decisions, it is very difficult to estimate the average effect. On the other hand, the existence of unexpected consequences is important from another perspective: Families' wellbeing could be higher if, hypothetically, people who make fertility decisions knew the consequences of childbearing that are currently unexpected to them. Thus, a reasonable state response to low fertility might be to support research on whether families on the whole would be better off with more children, and help disseminate research findings. It is not obvious that other types of family-level welfare disadvantages supposedly linked to low fertility can justify political interventions.
Keywords: C18; D80; I30; J13; J18; 330; below-replacement; bias; consequences; expected; fertility; methodological; physiological; policy; population; social; treatment-heterogeneity